INTERVENTIONS TO REDUCE EMERGENCY DEPARTMENT VISITS AND OPTIMIZE NURSING CARE - Melha Mosleh Ail Alyami, Ibrahim Muhammad Muhammad Al Dandour, Saeed Mofareh Abdullah Alqarni, Mohammed Ahmed Mannaa Al-Abdali, Nawaf Khaled Ayed Al Roumi, Mohammed Ali Mohammed Alothayqi,; Saeed Mohammed Hassan Alnashri, Mousa Atiah Muhaddili Alnashri, Mohammed Muabred Mohammed Alsayed, Hamza Ibrahim Abutalib Alabdali, Mohammed Ali Faiz Al Halafi (Chelonian Research Foundation, 2023)
Introduction: Telehealth and remote monitoring programs have been particularly effective, with studies indicating a reduction in ED visits by up to 30% for patients enrolled in these programs. The aim of this review is to systematically evaluate the existing literature and provide comprehensive insights into interventions that can significantly impact emergency department. Methods: A literature search was conducted across multiple electronic databases, including PubMed, MEDLINE, CINAHL, and Cochrane Library. The search was limited to studies published in the last ten years to ensure relevance and recency. The inclusion criteria were strictly defined to select relevant studies. Only peer-reviewed, interventional studies that explicitly measured the impact Of nursing interventions on the frequency of ED visits were included. Conversely, the exclusion criteria were set to maintain the focus and quality of the review. Studies were excluded if they were non-interventional, such as observational studies, reviews, commentaries, and case reports. Results: Seven interventional studies and clinical trials were meticulously analyzed, each contributing unique insights into the effectiveness Of various interventions in reducing emergency department (ED) visits and enhancing nursing care. The systematic review conclusively demonstrates that nursing-led interventions significantly reduce emergency department (ED) visits, with the examined studies showcasing a reduction range Of 20% to 40%. These interventions, encompassing telehealth, personalized care plans, patient education, and follow-up care, not only alleviate the strain on ED resources but also improve patient outcomes. Particularly noteworthy is the superior efficacy of nursing interventions compared to non-nursing led strategies in Similar domains, as indicated by the higher percentages Of ED visit reductions in the reviewed studies. Conclusions: "Ihe findings underscore the potential of nursing interventions as a key strategy in reducing ED overcrowding and enhancing the quality Of healthcare delivery, advocating for their broader implementation and integration into healthcare systems. Keywords: Intervention, Nursing, Efficacy, Emergency, Clinical Visits, Clinical Trial.